2001
DOI: 10.1385/endo:14:3:295
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Insulin-Stimulated Tyrosine Phosphorylation of Shc and Shc/Grb2 Association in Liver, Muscle, and Adipose Tissue of Epinephrine- and Streptozotocin-Treated Rats

Abstract: Shc protein phosphorylation has been extensively characterized as the initial step that activates a complex mitogenic pathway through its association with Grb2. In the present study, we investigated the adrenergic control of insulin-induced Shc phosphorylation and Shc-Grb2 association, and the modulating effect of streptozotocin-induced diabetes mellitus on Shc phosphorylation and Shc/Grb2 association. Acute treatment with epinephrine, which leads to a normoglycemic insulin-resistant state, does not affect ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…In VSMCs hyperglycemia results in increased proliferation and migration, and these responses are associated with enhanced MAPK activation (5). Similar observations have been reported in streptozotocin-induced diabetic rats that show an increase in Shc phosphorylation and Grb2 association with insulin stimulation (49). Our studies have shown that this enhanced MAPK activity is dependent upon increased Shc tyrosine phosphorylation and Grb2 association (3,5).…”
Section: Discussionsupporting
confidence: 88%
“…In VSMCs hyperglycemia results in increased proliferation and migration, and these responses are associated with enhanced MAPK activation (5). Similar observations have been reported in streptozotocin-induced diabetic rats that show an increase in Shc phosphorylation and Grb2 association with insulin stimulation (49). Our studies have shown that this enhanced MAPK activity is dependent upon increased Shc tyrosine phosphorylation and Grb2 association (3,5).…”
Section: Discussionsupporting
confidence: 88%
“…Interestingly, two markers of immature β-cells, Acox2 and Fzd2 [54], were overexpressed in EXP-ILS compared to both HLSC-ILS and human islets, which were respectively less and more differentiated. Notably, three genes for adaptor proteins involved in the transduction of insulin signal (GAB1, NCK1, SORBS1) [78, 79] were expressed at similar or higher levels in EXP-ILS compared to human islets, and were upregulated in respect to HLSC-ILS and HLSC, suggesting an increased activation of the insulin signaling pathway. Similarly, several markers of insulin secretion (CACNA1C, KCNJ11, KCNK3, PFKFB2, PIK3R2, SNAP25, VAMP2) [71, 8082] were expressed at similar or higher levels in EXP-ILS and human islets and were expressed at lower levels in HLSC and HLSC-ILS, suggesting an increased ability of EXP-ILS to release insulin granules.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of cold upon insulin signalling are tissue specific and within every tissue cold effects seem to be function‐specific, in such a way that they may positively influence some responses controlled by insulin and negatively influences others. Since increased sympathetic tonus is a major characteristic of cold‐exposed rats we believe that further characterization of molecular cross‐talk between insulin and adrenergic receptors (Klein et al 1999; Paez‐Espinosa et al 2001) may prove helpful in advancing the understanding of glucose homeostasis in cold‐exposed animals and disclosing new potential targets for therapeutics in diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%